TURKMOD: Developing a tax and benefit microsimulation model for Turkey - Kazim Okan Erol (University of Essex, Centre for Microsimulation and Policy Analysis (CeMPA), 2022)
This paper aims to study the income distribution and redistribution in Turkey by using a microsimulation analysis. Developing a Turkish tax and benefit microsimulation model allows the analysis of the Turkish public revenue system by using national SILC data. In this research, TRSILC input data have been transformed into a EUROMOD input dataset and included in the EUROMOD model, such that we can test the effectiveness of the Turkish tax and benefit system on data representative for Turkish private households. The aim of this study is to be able to compare the Turkish tax-benefit system with those of other European countries by implementing the same methodology. As a pioneering model, TURKMOD can be essential to assess the of the tax and benefit system on income inequality in Turkey.
Keywords: 330; Economics; Welfare Benefits; Taxation; Microsimulation